EXPLORING THE ROLE OF GREEN LOGISTICS TECHNOLOGIES AND MANAGERIAL COMMITMENT: A SYSTEMATIC LITERATURE REVIEW TOWARD A SUSTAINABLE SUPPLY CHAIN - Rizky Khoiriyah; Maniah Maniah (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
The growing pressure for sustainability has encouraged organizations to integrate environmental considerations into supply chain operations. Green Logistics Technologies (GLT) are widely recognized as key enablers for reducing environmental impacts and improving logistics efficiency. However, prior studies often examine technological adoption in isolation, with limited attention to the role of Managerial Commitment and Support (MCS) in ensuring that such technologies effectively contribute to Sustainable Supply Chain Performance (SSCP). This gap indicates the need for a more integrated understanding of how technological and managerial factors jointly drive sustainability outcomes. This study aims to systematically review and synthesize existing literature on the combined role of GLT and MCS in enhancing SSCP. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines, analyzing 50 peer-reviewed articles published between 2019 and 2025 and indexed in major academic databases. The findings reveal that GLT adoption significantly improves environmental and operational performance; however, its impact on SSCP is substantially strengthened when supported by strong managerial commitment, leadership engagement, and governance mechanisms. The review highlights that MCS functions as both a driver and a moderator in the GLT–SSCP relationship, ensuring strategic alignment, organizational readiness, and sustained sustainability outcomes. This study contributes theoretically by reinforcing the integration of the Resource-Based View and Institutional Theory in explaining sustainability-oriented supply chain transformation. Practically, it emphasizes that investments in green logistics technologies must be complemented by managerial capability development and organizational support to achieve long-term sustainable supply chain performance.